2021
DOI: 10.1007/s00894-021-04747-8
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of effects of pressure on paramagnetic, ferromagnetic, and antiferromagnetic spin-web Cu3TeO6

Abstract: The structure, electronic and magnetic properties have been investigated by the rst-principles calculations for paramagnetic, ferromagnetic and antiferromagnetic Cu 3 TeO 6 under pressure from 0 to 100 GPa. The calculated lattice parameters at 0 GPa are in excellent agreement with the available calculated and experimental values. With increasing pressure, the lattice parameters and volume decrease, but Cu 3 TeO 6 keep a stable cubic structure. The electronic calculations show that paramagnetic and ferromagneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The visualization of the Rietveld refined structure of Cu 3 TeO 6 is given in the inset of Figure . The formation of Cu 3 TeO 6 nanoparticle has been ensured with a crystal structure having a three-dimensional (3D) network grown from covalently bonded Cu and Te polyhedrons sharing oxygen atoms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The visualization of the Rietveld refined structure of Cu 3 TeO 6 is given in the inset of Figure . The formation of Cu 3 TeO 6 nanoparticle has been ensured with a crystal structure having a three-dimensional (3D) network grown from covalently bonded Cu and Te polyhedrons sharing oxygen atoms …”
Section: Resultsmentioning
confidence: 99%
“…Their study revealed that Cu 3 TeO 6 nanostructures have a Curie temperature below 64 K, indicating its antiferromagnetic behavior . Du et al investigated the pressure effect on the magnetic and electrical properties of antiferromagnetic spin-web Cu 3 TeO 6 using density functional theory . Despite many applications, Cu 3 TeO 6 has yet to be thoroughly investigated as a potential material for charge storage applications.…”
Section: Introductionmentioning
confidence: 99%